Hexaphosphate-derived phosphorus-functionalized carbon for lithium-ion battery anode - Gawli, Yogesh; Wahid, Malik; Fernandez, Rohan; Kothari, Dushyant; Shelke, Manjusha; Ogale, Satishchandra B. (Chemistryselect, 2017)
We show that high-temperature annealing of a dried hexaphosphate, namely phytic acid, renders activated (micro-porous) and phosphorus-functionalized graphene like carbon in a one-step process. At high enough temperature few volatile phosphates serve as porogen-forming entities while other groups reactively functionalize the carbon surface. The optimized material has high effective surface area due to the presence of defect states. As an anode material for Li-ion battery, it exhibits a reversible capacity that is double that of the graphite and is stable for 1000 cycles even at a high current of 5 A g(-1). This result is attributed to the concurrent presence of micropores and phosphorus containing groups in the carbon matrix.